FRAUD HEXAGON THEORY AND ACADEMIC FRAUD (COMPARATIVE STUDY ON STUDENT OF STIE SUTAATMADJA AND UNIVERSITI ISLAM SELANGOR) - Nunung Juliawati; Asep Kurniawan; Icih; Amirah Atiqah Binti Rizal (ZILLZELL MEDIA PRIMA, 2024)
This research aims to determine the difference in perceptions between STIE Sutaatmadja and University Islam Selangor students regarding the fraud hexagon theory (pressure, opportunity, rationalization, ability, arrogance or ego, and collusion) in academic fraud. The methode used in this research is a quantitative method with comparative studies, the sampling technique used in this research is simple random sampling and the sample criteria selected were students from STIE Sutaatmadja and University Islam Selangor. The data collection method used was a questionnaire method in the form of a questionnaire distributed via google form which was analyzed using IBM SPSS Statistic 25. The data analysis technique was the classic assumption test (normality test and homogeneity test) and the independent simple t-test and the men whitney non parametric test. The results of the research show that (1) there is a diffierence in perception regarding the pressure for academic cheating between STIE Sutaatmadja dan University Islam Selangor, there is no different perception regarding the opportunity (2), the rationalization (3), the ability (4), the arrogance (5), Collusion (6) and the academic cheating (7) for academic cheating between STIE Sutaatmadja and University Islam Selangor.